2015
DOI: 10.1111/gwat.12385
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Lakes in Groundwater Recharge and Discharge in the Young Glacial Area, Northern Poland

Abstract: The aim of this research was to delineate characteristic hydrogeological lake types in the Young Glacial Area (YGA). The YGA is in the central and east part of the Kashubian Lake District (KLD) in Northern Poland, an area covered by deposits of Quaternary glaciation. All the bigger lakes were investigated in the area of about 1500 km(2) (39 lakes). The role of lakes in groundwater recharge and discharge was determined from total dissolved solids (TDS) in lake waters and also from groundwater flow simulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Specific conductance measurements >100 µS/cm were measured in the lakes and wetlands situated on the glacial outwash or remnant tunnel valley features within the study area. Similarly, in the Young Glacial Area of northern Poland, Jaworksa-Szulc [13] found that recharge or losing lakes with low total dissolved solids (TDS) were commonly identified on till while discharge or gaining lakes with high TDS were commonly identified within glacial tunnel valleys. These results show the importance of hydraulic conductivity and position within the groundwater flow system for characterizing surface water and groundwater interaction [3].…”
Section: Specific Conductance Flow Paths and Mapped Glacial Sedimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific conductance measurements >100 µS/cm were measured in the lakes and wetlands situated on the glacial outwash or remnant tunnel valley features within the study area. Similarly, in the Young Glacial Area of northern Poland, Jaworksa-Szulc [13] found that recharge or losing lakes with low total dissolved solids (TDS) were commonly identified on till while discharge or gaining lakes with high TDS were commonly identified within glacial tunnel valleys. These results show the importance of hydraulic conductivity and position within the groundwater flow system for characterizing surface water and groundwater interaction [3].…”
Section: Specific Conductance Flow Paths and Mapped Glacial Sedimentsmentioning
confidence: 99%
“…More recently, Jaworksa-Szulc [13] used a groundwater model and TDS measurements to characterize how lakes interact with groundwater in the Young Glacial Area of northern Poland. Lakes that received groundwater discharge had TDS measurements that ranged from 250-350 mg/L while losing lakes or those that recharge groundwater measured less than 100 mg/L.…”
Section: Background and Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic processes of surface and groundwater systems are mainly influenced by the hydrological and hydrogeological conditions for integrated water resources management at watershed level [3]. Therefore, understanding surface and groundwater processes requires the understanding of the impact of geomorphology, hydrogeology, and climate on subsurface flow systems [4]. An integrated approach leads to conclusions related to how recharge and discharge are influenced under at Lake Karla watershed, Thessaly, Greece.…”
Section: Introductionmentioning
confidence: 99%